Analisa Pengamanan Data Teks Menggunakan Algoritma ADFGVX - Purnama, Chandra (MEANS (Media Informasi Analisa dan Sistem), 2018)
This study discusses the implementation of ADFGVX to encode text data. ADFGVX is one of the classic cryptographic methods that uses symmetry keys. this method uses a 6x6 key board for encryption and decryption. The process of encryption and decryption is done by grouping letters in bigram. By using a 6x6 key board, we can encrypt plainteks (original text data to be encrypted) and decrypt ciphertext (encrypted text data) by grouping it. Keyboards are generated randomly by software so that each encryption process (encryption and decryption) can use different keys. This software is also used to verify the results of ADFGVX encryption and decryption with the cube keyboard. ADFGVX software is developed using Visual Basic and graphically based languages in the Windows development environment.